Effectiveness of methodic system of motor functioning's preventive development in sixth year of children's life in their physical condition's improvement - L. L. Galamandjuk (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to determine effectiveness of simulated system of motor functioning's preventive development of pre-school children for improvement of their physical (motor) qualities at physical culture classes. Material: In research 5 years old children participated. In control groups they were 75 girls and 75 boys (25 with ambidexterity, 25 withright and 25 with left manual asymmetry). Experimental groups consisted of 60 girls and 60 boys (20 with every variant of manual motor asymmetry). Results: we registered positive influence of symmetric approach to training of children to main movements. It implies realization of all form of physical exercises' practicing in certain day of working week through creation of motor environment with aerobic mode of children's motor functioning. It is recommended to use breathing exercises with accent on relaxation and activation of functioning for regulation of mental state in required direction. Conclusions: for achievement of positive results it is important to take measures, oriented on home physical exercises. Interaction with parents for formation of children's conscious attitude and further practical realization of offered by us means and methods ensure more effective solution of this problem.